Variation of Hydraulic Resistance in Pressure Pipelines of an Open-Type Hydraulic System - Taras Sydor; Vadym Orel (Energy Engineering and Control Systems, 2024)
Pressure distributive pipelines with path distribution of fluid are part of various technical systems. Pressure losses at abrupt and smooth pipe reductions are components of total pressure losses in these pipelines. After all, the equalization of fluid distribution along the length of distributive pipelines is achieved, in particular, by reducing their diameter in the direction of flow. Depending on the configuration of the pipe reductions, pressure losses at this pipeline element can vary. For an open-type hydraulic system, a regulatory characteristics of pressure in the pipeline has been obtained with a constant fluid flow in a general form. The influence of measures necessary to change energy losses in the pipeline on the hydraulic resistance of the unregulated section of the pipeline has been taken into account. Options for these measures have been proposed for a pressure pipeline with pipe reduction.